Education in abortion care in Ireland: Medical Students For Choice (MSFC) taking a lead - O'Shea, Michael (Trinity Student Medical Journal, 2017)
Abortion is a common topic of discussion in Ireland. Provision of abortion care by healthcare workers is restricted in a number of ways by legislation. Among Medical Students and Non-Consultant Hospital Doctors, there is consensus that abortion care should be covered in core curricula. However, current evidence indicates these groups lack knowledge surrounding issues such as legislation and abortion care in an Irish context. Guidelines dealing with termination of pregnancy provide information on how best to support women considering abortion, however information provided by Government Organisations contains inaccuracies. Both fail to deal with issues surrounding abortion through online Telemedicine services, and legislative ambiguity may prevent healthcare workers from providing information which could make at-home abortions safer. This paper advises medical students and trainee doctors how best to deal with practical situations, such as women seeking advice on abortions overseas or through online providers. It provides a toolkit for clinicians to draw upon, which is in line with current legislation, guidelines and best practice. Further educational opportunities are available to students through Medical Students For Choice, through clinical attachments and student-led events. The educational benefits of such activities are discussed.